The Role of Tunneling in Doing Transfer Pricing - Moh. Ubaidillah (Profesional Muda Cendekia Publishing, 2023)
Transfer pricing practices carried out by companies by shifting profits from countries with high tax rates to countries with low tax rates, so as to minimize the tax burden in an effort to maximize company profits. In fact, tax revenue on income from multinational companies is a very significant part of tax revenues in the total tax revenues in the countries where these multinational companies operate. This study aims to determine the effect of profitability and taxes on transfer pricing with tunneling as a moderation variable. The study used secondary data as many manufacturing companies listed on the Indonesian Stock Exchange in 2019-2022. Sample selection using purposive sampling method which resulted in 40 manufacturing companies. This study used linear regression analysis with SPSS tools. The results of this study show that profitability and taxes have a significant positive effect on transfer pricing. Furthermore, tunneling is able to moderate the effect of profitability and taxes on transfer pricing.